Efficient synthesis and stabilization of poly(propylene carbonate) from delicately designed bifunctional aluminum porphyrin complexes1. Issue 26 (14th July 2015) - Sheng, Xingfeng; Wu, Wei; Qin, Yusheng; Wang, Xianhong; Wang, Fosong
<x xml:space="preserve">Abstract</x> Bifunctional aluminum porphyrin complexes were prepared, which showed good catalytic performance for copolymerization of propylene oxide and carbon dioxide, and the resulting poly(propylene carbonate) could be stabilized by treatment of aqueous HCl solution.